Periodontopathogens antibodies and major adverse events following an acute myocardial infarction: results from the French Registry of Acute ST-Elevation and Non-ST-Elevation Myocardial Infarction (FAST-MI). Issue 12 (20th June 2016) - Boillot, A; Range, H; Danchin, N; Kotti, S; Cosler, G; Czernichow, S; Meilhac, O; Puymirat, E; Zeller, M; Tchetche, D; Bouchard, P; Simon, T
Abstract : Background: Periodontopathogens antibodies have been shown to be associated with primary myocardial events, but little is known regarding their impact on major adverse events after a prior acute myocardial infarction (AMI). The present prospective study evaluates the association between antibody levels of 4 periodontopathogens and the risk of all-cause death or non-fatal myocardial infarction (MI) at 1 year in 975 patients admitted for acute ST segment or non-ST segment elevation MI in French Registry of Acute ST-Elevation and Non-ST-Elevation Myocardial Infarction (FAST-MI), a nationwide French survey. Methods: Multiserotype ELISAs were performed to assess levels of IgG and IgA against Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, Prevotella intermedia and Tannerella forsythia . Results: Adjusted HRs indicate the lack of association between IgG-anti- Po. gingivalis levels (0.96 (0.78 to 1.18)), IgA-anti- Po. gingivalis levels (1.13 (0.90 to 1.42)) and the risk of all-cause death or non-fatal MI at 1 year. Additionally, no significant association was found between the occurence of an event at 1 year and immunoglobulins levels against the others periodontopathogens. Conclusions: The present data indicate that circulating levels of periodontopathogens antibodies are not associated with an increased risk of major adverse events in patients with a prior AMI. Studies dealing with bacterial and clinical data are needed to assess the role of oral health in comprehensive cardiac rehabilitation programmes.